Prevalence and Radiological Evaluation of Work Related Musculoskeletal Disorder in Upper Extremity: Anatomical Insight and Public Health Implications of Wrist Pain - Saba Sharif, Solmaz Masood, Hira Bushra, Naheeda Perveen, Rafia Irum, Faiza Waseem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In modern world, use of computer has become increasing day by day. Prolonged use of computer in different offices may cause wrist pain or discomfort. Wrist pain occur in 50-60% of computer users who spent many hours working on computer either use of keyboard or mouse. Objective: To find the frequency of wrist pain in computer workers in different offices of Sheikh Zayed Hospital/Medical College Rahim Yar Khan. Methodology: Study Design was cross-sectional, Study setting area was different offices of Sheikh Zayed hospital/Medical College Rahim Yar Khan. Total 139 workers were selected as sample size through convenient sampling technique. Inclusion Criteria was; all computer workers who gave verbal consent and Exclusion criteria was; who didn’t give verbal consent and not willing to participate in study. Data Collection was carried out using a questionnaire which was developed and distributed among study subjects. Variables of questionnaire include age, computer usage hours, pain frequency and severity, breaks from work, pain type, pain occurrence time and effect of pain on daily activities, etc. Data and variables were analyzed in SPSS V23. Results: Out of 139 study subjects 73 subjects (52.5%) reported complain of wrist pain and out of all study subjects 61.9% of study subjects work on computer 7-8 hours daily and 36% works on computer 5-6 hours daily. Out of all study subjects 28.1% experience wrist pain during work, 6% experience wrist pain after work and 18% experience wrist pain both during and after work. Conclusions: Wrist pain in computer workers was very common. Almost half of the computer workers had complaint of wrist pain. Among the computer workers who had wrist pain, most of them spend 7-8 hours working on computer daily. Keywords: Frequency, Wrist pain, Computer use